Basic Characteristics of Road Traffic Deaths in China - Xujun Zhang; Hongyan Yao; Guoqing Hu; Mengjing Cui; Yue Gu; Huiyun Xiang (Tehran University of Medical Sciences, 2013)
Background: This study is to report characteristics of people killed in road traffic crashes and to describe major patterns of traffic crashes in China.Methods: Descriptive and inferential statistical analyses were conducted. Road traffic death national data, population denominator data and motor vehicles data of 2009 were obtained from the Bureau of Traffic Management at Ministry of Public Security and National Bureau of Statistics. The association between the fatalities from road traffic crashes and selected demographic factors, the time distribution, crash patterns, crash causes, and road user category were assessed in χ2 analyses.Results: Road traffic crashes in China disproportionably affected the following populations: males, persons 21-65 yr of age and adults aged more than 65 yr, persons living in rural areas, pedestrians, passengers, motorcyclists and bicyclists. Approximately 50% of fatalities of road traffic crash occurred in Eastern regions. The number of road traffic deaths was higher in daytime than in nighttime. Road traffic deaths in frontal crashes, side-to-side crash and crashes with an object or a person were more common than in rear-end crashes. In about 92% of road traffic deaths, auto drivers were believed to be responsible for the fatal crash. Major crash causing factors were speeding, careless driving, driving without a license, driving in the wrong lane, and driving after drinking alcohol.Conclusions: Road traffic deaths accounted for about 70,000 premature deaths in China which should be taken into account.